2001
DOI: 10.1063/1.1366656
|View full text |Cite
|
Sign up to set email alerts
|

La doped Ba1−xSrxTiO3 thin films for tunable device applications

Abstract: Pure and La doped Ba0.6Sr0.4TiO3 thin (BST) films were fabricated via the metalorganic solution deposition technique using carboxylate-alkoxide precursors on Pt–Si substrates. The La doping concentration, from 0 to 10 mol %, was found to have a strong influence on the 750 °C postdeposition annealed films material properties. All films possessed a nontextured polycrystalline microstructure with no evidence of secondary phase formation. The pure and 1 mol % La doped films exhibited a uniform microstructure sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(93 citation statements)
references
References 6 publications
1
92
0
Order By: Relevance
“…As shown in the figure, the dielectric constant rather slowly decreases with frequency up to 1 MHz. On the other hand, the dielectric loss of all samples does not show any appreciable dispersion with frequency up to 1 MHz indicating good interfacial characteristics between films and electrodes [18,19]. The dielectric constant and dielectric loss of Pb 0.3 Sr 0.7 (Ti 1−x Mg x )O 3 thin films at 1 MHz as a function of Mg content are illustrated in the inset of Fig.…”
Section: Resultsmentioning
confidence: 94%
“…As shown in the figure, the dielectric constant rather slowly decreases with frequency up to 1 MHz. On the other hand, the dielectric loss of all samples does not show any appreciable dispersion with frequency up to 1 MHz indicating good interfacial characteristics between films and electrodes [18,19]. The dielectric constant and dielectric loss of Pb 0.3 Sr 0.7 (Ti 1−x Mg x )O 3 thin films at 1 MHz as a function of Mg content are illustrated in the inset of Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Figure 4a shows the relationship between volume fraction and nominal molar fraction of CeO 2 in our BaTiO 3 -CeO 2 films on Pt(111). As discussed above, the volume fraction of CeO 2 phase starts to increase with the nominal molar fraction after the solubility limit of Ce in BaTiO 3 . Figure 4b shows the permittivity of the BaTiO 3 -CeO 2 films with different volume fraction of CeO 2 phase.…”
Section: Solubility and Self-assembled Composite Growth Of Batio 3 -Cmentioning
confidence: 98%
“…We also confirmed that either Ba or Ti doped CeO 2 films do not show any tunable behaviors (see figure 5), indicating that such fine BaTiO 3 nano-fibers in CeO 2 matrix (as observed in figure 3c) indeed act as a tunable element. 3 and CeO 2 resulted in nanocomposite structure, whose orientation was sensitive to the volume fraction of BaTiO 3 and CeO 2 . The inclined (obliquely-oriented) BaTiO 3 -CeO 2 composite film was grown at CeO 2 -rich composition.…”
Section: Solubility and Self-assembled Composite Growth Of Batio 3 -Cmentioning
confidence: 99%
See 1 more Smart Citation
“…6 For optimum performance of these microwave devices, the grown BST thin films should have large dielectric tunability ([⌬⑀ r /⑀ r ], ⑀ r is dielectric constant), low microwave losses (or high quality factor Q), and low temperature dependence of the dielectric constants in the operational frequency range of the device and in the corresponding temperature range. 11,12 In recent years much progress has been made in the deposition of high-quality BST films and increasing the performance of microwave devices based on BST thin films [13][14][15][16][17] ; however, the application of BST thin films in microwave devices is still hampered by their high microwave losses and the large temperature dependence of the dielectric constants. Furthermore, there is still concern about the reliability of microwave devices over the operating frequency and temperature ranges.…”
Section: Introductionmentioning
confidence: 99%